Democracy in the Digital Era as a Challenge and Opportunity for Public Participation - Endang Try Setyasih (Department of Public Administration, 2023)
Information and communication technology (ICT) has brought about significant changes in the political system and government, especially in facilitating public participation and promoting democratic values. This paper discusses the challenges and opportunities faced in strengthening public participation in democracy in the digital era. This study uses a descriptive qualitative approach with a literature and data review method to discuss the extent to which ICT can increase public participation in the context of democracy. The research results show that information and communication technology provides new opportunities for public participation in political and governmental processes. Public participation through democracy in the digital era can increase accessibility, speed up the decision-making process and increase transparency in government. However, challenges such as the digital divide, information trust and security, and lack of organized citizen participation must be overcome